Competetiveness of the cotton value chain in Africa - Sall, Leysa M.; Odjo, Sunday P.; Zaki, Chahir (AKADEMIYA2063, 2023)
Cotton production and trade have a long history and important role in Africa, dating back centuries before the colonial period. While the sector saw several developments in the post colonial period, cotton trade remained primarily in unprocessed cotton because of several structural challenges affecting its production. Moreover, African exports of cotton have decreased in recent years from a total annual average of US$55 billion1 in the 2006–2010 period to $48 billion in the 2017–2021 period. At the same time, cotton imports increased by 37 percent, up from $37 billion to $51 billion, making Africa a net importer in the later period. At the value chain level, unprocessed cotton products have the lion’s share in the export market, accounting for about 12 percent of global exports of raw cotton during the 2017–2021 period. Africa’s semi-processed and processed cotton product exports account for 2 percent and 3 percent, respectively, for the same period. In addition, African imports of processed cotton increased as a share of world cotton trade (from 3 percent to 4 percent) over the two periods.